Linguistic Competencies for the Entrepreneurial Culture Development - SIZOVA, YULIYA S.; ORLOVA, LIUBOV N.; LAVRENTJEVA, EKATERINA A. (The journal of contemporary issues in business and government, 2021)
One of the critical objectives of modern societies is promoting entrepreneurship as the basis of economic stability, which is accomplished developing the entrepreneurial way of thinking and entrepreneurial competences in the participants of economic processes. A growing number of people nowadays strive to accommodate business knowledge in their personal development. However, beyond business knowledge, the implementation of entrepreneurial initiatives also requires language competences; that is, the skills of communicating in various linguistic environments. The purpose of this study is to establish the role of language competences for the development of entrepreneurial culture and the potential of implementation of international business projects. The methods of qualitative content analysis and semantic analysis are used in this study to explore and provide insight to existing scientific concepts. The statistical method is used to consider the previously obtained analytical information. This made it possible to identify the need to develop language competences for entrepreneurial culture boosting. Following the research, a conceptual model of building language competences has been proposed as a tool for developing an entrepreneurial culture in individuals.